Dispersion cooligomerisation of mixture of C9 fraction unsaturated hydrocarbons - Orobchuk, Oksana; Fuch, Ulyana; Subtelnyy, Roman; Dzinyak, Bohdan (Lviv Polytechnic Publishing House, 2015)
Improving the technology for producing cooligomers (syntheticlow molecular petroleum resins), which are obtained from chaep petrochemical raw materials – hydrocarbon fractions of liquid by-products of pyrolysis (LBPP) or cracking of oil, refining products or gas was discussed in the paper. The imperfections of industrial methods of initiated oligomerization are high reaction temperature , high reaction time, complexity of the selection of target products, high enough color. З метою усунення недоліків, властивих виробничим процесам, запропоновано проводити процес дисперсійної коолігомеризації To eliminate the shortcomings inherent in the production process to carry out the process of dispersion oligomerization is proposed. A technological two-stages scheme of process of cooligomers obtaining by dispersion methods with next solution cooligomerization of unreacted hydrocarbons of C9 fraction has been designed. Results are of practical interest in refining by-products of pyrolysis of diesel fuel.
Keywords: liquid pyrolysis products; dispersion cooligomerization; C9 fraction; the initiator; cooligomer